Metabolic profiles identify markers of catch-up growth in children born small for gestational age (SGA). (24th May 2012) - Butcher, I; Whatmore, A; Bonshek, C; Shaikh, G; Dunn, W; Brown, M; O'shea, E; Victor, S; Powell, P; Settle, P; Padmakumar, B; Tan, A; et al.
Abstract : The majority of children born SGA exhibit catch-up (CU) growth in the early years of life. However, 10% do not catch-up (NCU) [∼2000 per annum in the UK) and become eligible for GH treatment at age 4 years. All these SGA babies, in particular those with CU, have an increased risk of vascular and metabolic disease in later life. A marker of future growth pattern would allow early lifestyle intervention for those destined to CU and earlier GH treatment for the NCU. Metabolomics can be used to characterise and quantify small metabolites and metabolic intermediates in blood and urine. We have therefore compared metabolomic profiles in prepubertal children born SGA who have exhibited either CU or NCU growth. Samples were taken from 23 children at mean age of 5.7 ± 1.9 years in NCU and 6.2 ± 1.1 years in CU. 16 blood samples (7 NCU, 9 CU) and 19 urines (10 NCU, 9 CU) were analysed. Both groups had comparable birth weight SD scores: NCU −2.6 ± 1, CU −2.5 ± 0.4. The CU group had a current height SD score of −0.4 ± 1.1 versus −3.2 ± 0.9 in the NCU group (p<0.001). Samples were analysed by mass spectrometry coupled to either gas or liquid chromatography. In urine, myo-inositol (involved in insulin and IGF signalling) was 5-fold lower in CU compared to NCU (p=0.03), while uric acid and carnitine were 2-fold higher (p=0.007 & p=0.03 respectively). In serum, 3 amino acids, asparagine (p=0.03), glutamine (p=0.03) and serine (p=0.04), were 2-fold higher in CU compared to NCU. CU had significantly higher levels of bile acids, vitamin D metabolites and glycerophosphotidylcholines and decreased levels of sphingolipids compared to NCU. Conclusion: There are significant differences in mid-childhood in metabolic profiles of CU versus NCU children born SGA, with such discrepancies potentially affecting growth. We plan to undertake metabolomic studies in the first year of life prior to CU growth occurring to define early biomarkers of CU versus NCU growth.